The Relationship between Da'wah and the Principles of Islamic Economics (Socio-Historical Success of the Prophet Muhammad's Da'wah) - Nazarudin (Konsultan Jurnal Ilmiah Indonesia, 2026)
The Prophet Muhammad's preaching was not only oriented toward spiritual transformation but also touched on the social and economic dimensions of Arab society. This article aims to analyze the relationship between preaching and Islamic economic principles from a socio-historical perspective as a contributing factor to the success of the Prophet Muhammad's preaching. This research uses a qualitative approach with library research, drawing on sources from the Quran, Hadith, and classical and contemporary Islamic historical and economic literature. The results indicate that Islamic economic principles such as monotheism, justice, honesty, balance, the prohibition of usury, and strengthening social solidarity through zakat and sadaqah played a significant role in building social trust and economic stability. The implementation of these principles not only improved the economic order but also strengthened the moral legitimacy of the Prophet Muhammad's preaching within the communities of Mecca and Medina. Thus, the relationship between preaching and Islamic economics is integrative and mutually reinforcing, serving as a crucial foundation for the success of Islamic preaching in its early development. This study is expected to provide a conceptual contribution to the development of Islamic preaching oriented toward social justice and the welfare of the people in the contemporary era.